Pendidikan Multikultural dalam Budaya Nemui Nyimah - Muhammad Candra Syahputra (UIN Mataram, 2020)
Indonesia is a country that consist of various tribes, cultures, customs, religions and beliefs. This has become a special asset for the Indonesian people, but on the other hand it has also been disastrous because it can cause conflict with the another. Therefore the need to instill multicultural in people’s lives, certainly through education. Multicultural education should be taken from existing local wisdom, in here the author will take the local wisdom of Lampung which is called nemui nyimah as the basis of multicultural education in Lampung. This research uses a qualitative approach, with the literature study method, with in-depth analysis based on available data sources. The resukts of this study that the culture of nemui nyimah contained multicultural values such as sharing with guests, being friendly to guests, good manners, being generous with guests, which later could be developed in a formal education environtment.